Letter : Clothing for Spanish refugees - Tewson, Vincent
032-0032-001 INTERNATIONAL. HVT/EAB. 8th August 1939. Mr. A. Conley, Nat. Union of Tailors & Garment Workers, Union Chambers, 20, Park Place, LEEDS. Dear Mr. Conley, CLOTHING FOR SPANISH REFUGEES. For your information I am enclosing copy of a letter which I have received from Mr. Sullivan, your London No. 1 Branch Secretary, informing us of several offers he has had in respect of clothing for Spanish refugees now in France. I am also enclosing copy of my reply from which you will see that we have accepted the offers made and have suggested a form of procedure in respect of the consignment of the goods to France. With best wishes, Yours sincerely, Assistant Secretary. 292/946/32/32